The role of innovation characteristics in the adoption of Integrated Pest Management (IPM) practices by paddy farmers in Iran - Ghane, Feloor; Abu Samah, Bahaman; Ahmad, Aminah; Idris, Khairuddin (Centre for Extension, Entrepreneurship and Professional Advancement (APEEC), Universiti Putra Malaysia, 2010)
The purpose of this study is to explore the effect of innovation characteristics in adoption of integrated pest management (IPM) practices by paddy farmers in three provinces of Iran. A total of 190 paddy farmers were selected by using proportional stratified sampling. Data collection was done by a set of questionnaires that was administrated through personal interview. Validity of the questionnaire was confirmed by a panel of experts. To assess the reliability of the questionnaire, Cronbach’s alpha was used. The results of structural equation modelling showed that the hypothesized model fit the data. There are positive and direct relationship between compatibility and trial ability of and adoption of IPM practices.